Pelatihan Ketrampilan Pengurusan Jenazah Perempuan Melalui Metode Simulasi Peer Teaching Bagi Ibu-Ibu Fatayat Senjayan Gondang Nganjuk - Ubaidillah, M. Burhanuddin; Ristianah, Niken; Mustofa, Idam; Jihad, Zayyin Alfi; Hamdi, Mustafid; Fitriah, Aini; Wasi’ah, Siti (LP3M STAI Darussalam Krempyang Nganjuk, 2018)
Islam takes a close interest in mortal management as one of the human relationships with other human beings after death. The cure is a human right and obligation for Muslims to do it with the best management. The law governing the body is fardhu kifayah. That is, when solved one person then another commitment is lost. In the guidance of Islam, close families are more interested in bathing and treating the body to anticipate the disgrace of the body. In the community's view, the person in charge of custody treatment is Modin. Everything related to the care needs of the corpse is left to Modin. The community considers it unnecessary to know how to take care of the body from the beginning to finish because it has its personnel. The bodyguard practice is still in Senjayan hamlet. Whenever someone dies, especially women, they are reluctant to take care of themselves independently. It's always a good idea of ​​how to care for a woman's body. The training of women bodybuilding is aimed at equipping Fatayat and Muslimat Mothers of Senjayan Village with excellent and actual custody of the bodies based on the Islamic Shari'ah. As a follow up of this program, Fatayat and Muslimat mothers are willing to take care of the woman's body independently.